The public's role in COVID-19 vaccination: Human-centered recommendations to enhance pandemic vaccine awareness, access, and acceptance in the United States. Issue 40 (24th September 2021) - Schoch-Spana, Monica; Brunson, Emily K.; Long, Rex; Ruth, Alexandra; Ravi, Sanjana J.; Trotochaud, Marc; Borio, Luciana; Brewer, Janesse; Buccina, Joseph; Connell, Nancy; Hall, Laura Lee; Kass, Nancy; et al.
Highlights: A thoughtful vaccination campaign is critical to ensure COVID-19 vaccine uptake. Social, behavioral, and communication science is essential to such a campaign. Meaningful messages from trusted spokespersons can crowd out misinformation. COVID-19 vaccines must be available at familiar, convenient locations that feel safe. Transparent decisions and public oversight mechanisms strengthen vaccine confidence. Abstract: Given the social and economic upheavals caused by the COVID-19 pandemic, political leaders, health officials, and members of the public are eager for solutions. One of the most promising, if they can be successfully developed, is vaccines. While the technological development of such countermeasures is currently underway, a key social gap remains. Past experience in routine and crisis contexts demonstrates that uptake of vaccines is more complicated than simply making the technology available. Vaccine uptake, and especially the widespread acceptance of vaccines, is a social endeavor that requires consideration of human factors. To provide a starting place for this critical component of a future COVID-19 vaccination campaign in the United States, the 23-person Working Group on Readying Populations for COVID-19 Vaccines was formed. One outcome of this group is a synthesis of the major challenges and opportunities associated with a future COVID-19 vaccination campaign and empirically-informed recommendations to advance public understanding of, access to, and acceptance of vaccines that protect against SARS-CoV-2. While not inclusive of all possible steps than could or should be done to facilitate COVID-19 vaccination, the working group believes that the recommendations provided are essential for a successful vaccination program.